(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article considers the phenomenon of procrastination in the context of different cultures and time. The concept of “procrastination” is investigated; the relevance of this phenomenon and the laws of its growth are determined. The results of an empirical study of the spread of this phenomenon among young people are presented. The reasons for the existence of procrastination in adolescence are clarified. Factors contributing to an increase in the level of procrastination have identified. Highlighted modern approaches to the problem and described the main types of procrastination. The mechanism of its work is shown and the main types of procrastinators are presented. A list of distractions has been compiled and psychological-pedagogical recommendations developed to prevent procrastination.